2021
DOI: 10.1108/imds-01-2021-0015
|View full text |Cite
|
Sign up to set email alerts
|

Empirical identification of skills gaps between chief information officer supply and demand: a resource-based view using machine learning

Abstract: PurposeThe role of emerging digital technologies is of growing strategic importance as it provides significant competitive advantage to organisations. The chief information officer (CIO) plays a pivotal role in facilitating the process of digital transformation. Whilst demand continues to increase, the supply of suitably qualified applicants is lacking, with many companies forced to choose information technology (IT) or marketing specialists instead. This research seeks to analyse the organisational capabiliti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…, 2021). Other research has looked at TAs as suitable players in developing training and mentoring schemes that can help mitigate skill gaps in the job market such as the high demand for qualified chief information officers (CIOs) (Barnes, Rutter, La Paz, & Scornavacca, 2021) or the digital skills training of supply chain workers (Foroughi, 2020). Fiehn et al.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…, 2021). Other research has looked at TAs as suitable players in developing training and mentoring schemes that can help mitigate skill gaps in the job market such as the high demand for qualified chief information officers (CIOs) (Barnes, Rutter, La Paz, & Scornavacca, 2021) or the digital skills training of supply chain workers (Foroughi, 2020). Fiehn et al.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…redefining the business model (Mues et al, 2021), providing high-quality information to their customers (Spiegel, Weiss, Stoycheva, Canis, & Ihler, 2021) or collaborating between the government, industry and academia (Fitnawan et al, 2021). Other research has looked at TAs as suitable players in developing training and mentoring schemes that can help mitigate skill gaps in the job market such as the high demand for qualified chief information officers (CIOs) (Barnes, Rutter, La Paz, & Scornavacca, 2021) or the digital skills training of supply chain workers (Foroughi, 2020). Fiehn et al (2020) found that the professional association of German rheumatologists is a key stakeholder in ensuring optimal care for all patients through appropriate delegation of medical duties and treatments.…”
Section: Trade Associations and Digital Transformationmentioning
confidence: 99%
“…Thus, mentoring is seen as a short-term one-on-one process that is directly associated with increased knowledge sharing (Curtis and Taylor, 2018); the experienced employees provide guidance to newcomers regarding content knowledge, required abilities (Al-Zoubi et al. , 2020; Barnes et al. , 2021), and ways of thinking and behaving (Geeraerts et al.…”
Section: State Of the Artmentioning
confidence: 99%
“…Classical knowledge sharing strategies focus on the knowledge flows that pass from experienced to the less experienced employees. Thus, mentoring is seen as a short-term one-on-one process that is directly associated with increased knowledge sharing (Curtis and Taylor, 2018); the experienced employees provide guidance to newcomers regarding content knowledge, required abilities (Al-Zoubi et al, 2020;Barnes et al, 2021), and ways of thinking and behaving (Geeraerts et al, 2018). Mentoring often complements training, which is a traditional classroom-style event (courses, seminars, workshops) that focuses on transforming individually shared knowledge into collective knowledge (Krull et al, 2022;Lim et al, 2022), the trainer acts as a knowledge diffuser, while the trainees act as passive knowledge receivers, storing the acquired knowledge as shared meanings and mental models.…”
Section: Organizational Strategies To Avoid Corporate Amnesiamentioning
confidence: 99%
“…A digital supply chain (DSC) electronically delivers products from origin to destination [9]. DSC helps increase responsiveness, flexibility, and agility [10].…”
Section: Introductionmentioning
confidence: 99%